1998
DOI: 10.1038/sj.bjp.0701592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term treatment with trandolapril on sarcoplasmic reticulum function of cardiac muscle in rats with chronic heart failure following myocardial infarction

Abstract: 1 Calcium transport activity of isolated cardiac sarcoplasmic reticulum (SR) including Ca 2+ uptake and release is decreased in animals with chronic heart failure (CHF) following myocardial infarction. The present study was undertaken to determine whether an angiotensin converting enzyme (ACE) inhibitor, trandolapril, improves cardiac sarcoplasmic reticular function in animals with CHF following myocardial infarction. 2 CHF was induced by left coronary artery ligation in rats, which resulted in an infarction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…These findings are in agreement with previous reports on the MI model of CHF (1,2,34,40,41). The depression in SR Ca 2ϩ uptake appears to be related to the SR Ca 2ϩ pump mechanism, because SR Ca 2ϩ -stimulated ATPase activity was also decreased in MI-induced heart failure.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are in agreement with previous reports on the MI model of CHF (1,2,34,40,41). The depression in SR Ca 2ϩ uptake appears to be related to the SR Ca 2ϩ pump mechanism, because SR Ca 2ϩ -stimulated ATPase activity was also decreased in MI-induced heart failure.…”
Section: Discussionsupporting
confidence: 94%
“…A similar magnitude of depression (ϳ50%) in the SR Ca 2ϩ release channel in the failing heart was apparent when it was monitored by two different techniques: Ca 2ϩ -induced Ca 2ϩ release and ryanodine receptor binding assay. Our results for Ca 2ϩ release and Ca 2ϩ uptake activities obtained by employing isolated SR preparations are similar to those of other investigators (40,41) who assessed the SR Ca 2ϩ transport activities in the infarcted hearts by employing skinned fiber preparations. Because SR Ca 2ϩ release and Ca 2ϩ uptake are intimately involved in the processes of cardiac contraction and relaxation, respectively, the observed depression in SR Ca 2ϩ release and Ca 2ϩ uptake activities may explain the reduction in cardiac ϩdP/dt and ϪdP/dt in the failing heart.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…11,12 There is indirect evidence that ACE inhibitors can affect SR function because it has been reported that several ACE inhibitors antagonize the changes in SR calcium uptake or release observed in different experimental models of heart failure. [13][14][15][16][17][18][19] It is however uncertain whether these observations reflect a direct effect on SR proteins or are rather a nonspecific consequence of the improved cardiac function. Therefore, it seemed interesting to investigate whether zofenopril may modulate SR function.…”
Section: Introductionmentioning
confidence: 99%